Formation of Monolayer Polystyrene Array Template for Gold Nanomesh Structure - Morsin, Marlia; Razali, Nur Liyana; Mat Salleh, Muhamad; Zainal, Nurfarina; Morsin, Marriatyi (International Journal of Integrated Engineering, 2018)
In this study, the preparation of monolayer array template was performed using 0.2 µm polystyrene (PS) nanospheres monodisperse micro particle deposited onto Indium Tin Oxide (ITO) coated glass substrate. The template was used to arrange the gold (Au) in nanomesh structure thus, enhance its homogeneity for having better sensitivity and repeatability in the plasmonic sensor application. PS nanosphere template was prepared by diluting 0.2 µm PS liquid with ethanol in the ratio of 1:3 and stirred with 400 rpm for 1 hours at 40 °C. Next, the PS solution was spin coated on ITO substrate at different speed variation starting from 200 rpm to 800 rpm in 3 minutes at room temperature. The template structure was then inspected with Field Emission-Scanning Electron Microscopy (FESEM). It was found that, the PS nanosphere template with 600 rpm speed shows the most orderly arrangement of PS array. Subsequently, the PS array template was used as a mask to deposit gold (Au) and performed via direct current (DC) sputtering method. Finally, the Au nanomesh structure was obtained using the lift ‒ off process of PS nanosphere template.